Metal–Organic Charge Transfer Complexes of Pb(TCNQ)2 and Pb(TCNQF4)2 as New Catalysts for Electron Transfer Reactions. Issue 21 (9th September 2020) - Hussain, Zakir; Zou, Wenyue; Murdoch, Billy J.; Nafady, Ayman; Field, Matthew R.; Ramanathan, Rajesh; Bansal, Vipul
Abstract: The fundamental properties and applications of organic charge transfer complexes based on Pb(TCNQ)2 (Pb = lead, TCNQ = 7, 7, 8, 8‐tetracyanoquinodimethane) and its fluorinated derivatives are relatively unknown. Here, a facile solid–liquid approach for the synthesis of Pb(TCNQ)2 and Pb(TCNQF4 )2 is reported. These materials are thoroughly analyzed to obtain insights into their unique morphological, vibrational and optical properties, the latter extending across the UV–Vis–IR region. Subsequently, the catalytic potential of these materials is evaluated by employing a model redox reaction, which revealed two orders of magnitude higher catalytic activity of the fluorinated derivative over non‐fluorinated Pb(TCNQ)2 crystals. Overall, the work presented here adds a new member to the growing yet limited library of metal–organic charge transfer complexes and validates the outstanding redox catalysis performance of this group of materials. Abstract : New non‐transition metal‐based metal–organic charge transfer semiconductors of TCNQ (TCNQ = 7, 7, 8, 8‐tetracyanoquinodimethane) derivatives are reported as outstanding catalysts to promote redox reactions. The fluorinated Pb(TCNQF4 )2 derivative is observed to show two orders of magnitude higher catalytic efficiency over Pb(TCNQ)2 . The work opens new opportunities to expand the repertoire of TCNQ‐based charge transfer complexes for a myriad of applications.